The Ivory Trail - Mundy, Talbot, 1879-1940 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Ivory Trail" by Talbot Mundy is a novel written during the early 20th century. The story follows the adventures of Monty and his companions, who find themselves enmeshed in a quest for a legendary hoard of ivory linked to the notorious Arab slave trader, Tippoo Tib, while navigating the complexities of colonial politics and personal ambitions in Zanzibar and beyond. The opening portion of the novel introduces the key characters, primarily focusing on Monty, a cavalry officer who inherits the title of Earl but finds himself financially constrained. After a harrowing experience at sea, Monty and his companions land in Zanzibar, where they are kept in quarantine. Amidst the bureaucratic tedium, discussions about the vast untapped riches of ivory buried by Tippoo Tib ignite their adventurous spirits. As they meet colorful characters, including a mysterious old attendant with potential ties to the ivory secret, they begin to formulate a plan to track down the lost treasure. The atmosphere is rich with intrigue, humor, and the promise of adventure as they seek out clues that may lead them on a remarkable journey into the heart of Africa. (This is an automatically generated summary.)
Release date is 2004-02-01
Produced by Jake Jaqua
Keywords: Africa -- Fiction; Adventure stories